The role of the Self in assessing doping cognition: Implicit and explicit measures of athletes' doping-related prototype perceptions. (May 2016) - Whitaker, L.; Petróczi, A.; Backhouse, S.H.; Long, J.; Nepusz, T.
Abstract: Objectives: To examine athletes' implicit and explicit prototype perceptions of performance enhancing substance (PES) users and non-users. Design: A cross-sectional mixed-method study. Methods: Competitive athletes from 39 sports (N = 226; mean age = 27.66 ± 9.74 years; 59% male) completed four self-report questions and two Brief Implicit Association Tests online, assessing prototype favourability and similarity of PES users and non-users. Results: Athletes explicitly associated themselves with a non-user (M = 3.13 ± 0.92) more than a PES user (M = 0.56 ± 0.88) and perceived a non-user (M = 89.92 ± 14.98) more favourably than a PES user (M = 13.18 ± 21.38). Indexing behaviour on self-reports, doping contemplators did not differ from 'clean' athletes in their perceptions of PES user prototypes while dopers perceived PES users favourably and similar to themselves. In comparison, doping contemplators paired the concept of 'dopers' easier with themselves than with others, while clean athletes and dopers had no preference for either pairing (D = −0.33, -0.08 and 0.01, respectively). All groups demonstrated some degree of preference for 'good and doper', moving from slight to moderate to strong preference in the groups of clean athletes, dopers and contemplators, respectively (D = −0.20, −0.37 and −0.80, respectively). Conclusions: Results suggest that doping contemplators may have a positive bias towards doping which is not endorsed in self-reports. Implicit preferences, along with the disparity between the implicit and explicit measures of athletes' doping-related prototype perceptions advance understanding of doping behaviour and make a unique contribution to research methodology. Factors influencing the interplay between explicit and implicit endorsements of PES user prototypes warrant further research. Highlights: Contrasting findings emerged between implicit and explicit prototype perceptions. Athletes explicitly associated themselves with a non-user more than a PES user. Non-users were explicitly viewed more favourably than PES users. B-IAT suggests doping contemplators have a strong preference for good and doper. B-IAT suggests doping contemplators have a slight preference for me and doper.